Interfacial shear strength and tensile properties of injection-molded, short- and long-glass fiber-reinforced polyamide 6,6 composites - Hassan, A.; Yahya, R.; Rafiq, M.I.M.; Hussin, A.; Sheikh, M.R.K.; Hornsby, P.R. (2011)
Injection-molded short- and long-glass fiber/polyamide 6,6 composites were subjected to tensile tests. To measure the effectiveness of the fibers in reinforcing the composites, a computational approach was employed to compute the fiber-matrix ISS, orientation factor, reinforcement efficiency, tensile-, and fiber length-related properties. Although the LFCs showed great improvement in fiber characteristics compared to the SFCs, enhancement in tensile properties was small, which is believed to be due to the larger fiber diameter. Kelly-Tyson model provides good approximation for the computation of ISS and tensile-related properties.